Examining risk as guideline in design stage for green retrofits projects: a review - M. S. N., Lee; Masrom, M. A .N.; Mohamed, S.; K. C., Goh; Sarpin, N.; Manap, N. (2020)
Green buildings have generally been adopted as strategy towards sustainable development to reduce greenhouse gas. The implementation of green concept recently has widely spread over the year. However, the positive impact to the environment is still low due to heavily focus on new construction project as compare with retrofitting the existing building. A retrofit practice is not only regaining overall existing building appearance, but the improvement towards energy efficiency is remarkably significant at the expense of huge challenges and risk. As a consequence, retrofit practitioner is confronting an assortment of risks at the early stage of the project. Given that, green retrofit concept is emerging research area to Malaysia construction industry which motivates to determining the risk involve in design stage. This paper aims to review risk in design stage for green retrofit project for commercial buildings through gathering comprehensive literature review. As a result, two main category risks in design stage (technical/quality risk and financial management risk) is determined and extracted to identify risk. These risks are then quantified through analysis to enhance design performance within costbenefit. The proposed conceptual framework model is expected to assist retrofit practitioner to identify risk and obtain feasible retrofit strategy.